An Objectivizing Description of Religious Experience: What is it Like for Thomas Aquinas to be a Bat? - Oniščik, Marija (Religija ir kultūra, 2010)
The philosophy of St Thomas Aquinas is directed towards theology both as the language of God and the language about God. It concerns meaningfulness, functionality, and proper use of language. The Thomistic theory of language is based on the main Aristotelian principles: an empirical condition of knowledge and isomorphic relationship between language and reality. A process of conceptualization beginning with empirical perception becomes crucial for this adequacy. However, if in Aristotelian view the reality is postulated as objectively existing over there, Thomas Aquinas is not contented with such a realistic stand, especially as his philosophy deals not only with natural reality, but also with supernatural one, integrating them into one onto-theo-logical complex.A short outline of Thomistic theory of language shows that a chain of signification, in which a word denotes its sense, verbal sense refers to a mental concept, and a concept is an understood form of empirically perceptible reality, does not account for the onto-theo-logical sort of reality, experienced as unspeakable. Speaking about God as well as speaking about being is possible only by means of description which converts an inward “mystic” experience of such a reality into an objective understandable knowledge and serves as a demonstration of reality in question. The example of a bat, taken from Aquinas and Nagel, shows that such a demonstration is properly possible not by use of metaphor, but by analogical way of speaking.
Keywords: onto-theo-logia; conceptualization; sense; description; metaphor; analogy